2023
DOI: 10.1002/chem.202203803
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Conjugated Oligoelectrolytes Containing Triphenylphosphonium Solubilizing Groups

Abstract: Conjugated oligoelectrolytes (COEs) are an emerging class of amphiphilic antimicrobial compounds with a modular molecular framework suitable for simple chemical derivatization. Here, a series of COE derivatives with a stilbene-conjugated segment and triphenylphosphonium (TPP) pendant groups was designed and synthesized to understand how lipophilic cationic groups impact antimicrobial activity. In vitro evaluations against ESKAPE pathogens showed broad-spectrum activity towards multi-drug resistant (MDR) bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The lipid bilayer-mimicking distribution of hydrophobic and hydrophilic domains promotes spontaneous membrane intercalation and environment-specific fluorescence emission. , These features distinguish COEs from other optical reporters that either associate with specific targets or are anchored to the lipid bilayer by hydrophobic domains . The high biocompatibility and tunable physicochemical and photophysical properties of MICOEs have allowed for biological applications, including labeling or killing microorganisms, tracking extracellular vesicles, and cell imaging. Despite these promising applications, little is known about the molecular features that influence interactions of COE with mammalian cells, particularly within subcellular organelles. In the case of COE-S6 , a representative cationic oligo-phenylenevinylene (oligo-PV) COE, previous colocalization studies demonstrated no mitochondrial association, instead it localizes exclusively within lysosomes upon cellular internalization, as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…The lipid bilayer-mimicking distribution of hydrophobic and hydrophilic domains promotes spontaneous membrane intercalation and environment-specific fluorescence emission. , These features distinguish COEs from other optical reporters that either associate with specific targets or are anchored to the lipid bilayer by hydrophobic domains . The high biocompatibility and tunable physicochemical and photophysical properties of MICOEs have allowed for biological applications, including labeling or killing microorganisms, tracking extracellular vesicles, and cell imaging. Despite these promising applications, little is known about the molecular features that influence interactions of COE with mammalian cells, particularly within subcellular organelles. In the case of COE-S6 , a representative cationic oligo-phenylenevinylene (oligo-PV) COE, previous colocalization studies demonstrated no mitochondrial association, instead it localizes exclusively within lysosomes upon cellular internalization, as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%